CORRELATIONS AND HERITABILITY OF THE CHARACTERS DETERMINING THE SEED YIELD OF THE PANICLE INFLORESCENCE FORMS OF ALFALFA (MEDICAGO X VARIA T. MARTYN) - Bodzon, Zbigniew (Plant Breeding and Seed Science, 2016)
Phenotypic correlation coefficients and heritability of the characters determining seed yield of panicle inflorescence forms of alfalfa was examined. Seed yield per plant, which was positively correlated with 10 generative and morphological traits, depended upon the number of pods per panicle and the number of seeds per pod. Variability of these characters determined about 60% of the variability of seed yield. Multiple linear regression and phenotypic correlations show that simultaneous selection for increased pod number per panicle and increased seed number per pod and number of branches per panicle resulted in enhanced seed yield potential. The share of the additive genetic effects in the phenotypic variance for number of pods per panicle was low and about 23%, while for number of seeds per pod and seeds per panicle amounted to about 75-77% and 56-57% respectively.